Innocent as sin - Lowell, Elizabeth, 1944-; Monda, Carol (New York : HarperAudio, 2007)
From multi New York Times bestseller Elizabeth Lowell comes another thrilling novel of romantic suspense.
HarperAudio: UACD 5567(9)
Unabridged.
Read by Carol Monda.
7 13 25 26 33
Keywords: Talking books; Audiobooks